KEWAJIBAN PAJAK SUBJEKTIF DAN OBJEKTIF UNTUK MENENTUKAN KEWAJIBAN MEMILIKI NPWP - Lusy Suprajadi (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
Anyone who has fulfilled conditions both subjective and objective according to income tax law must have tax identification number (NPWP). Tax identification number is a number issued to taxpayers by the tax office to identify taxpayers and to assist them in fulfilling their tax obligations. Conversely, NPWP should withdraw when tax payers do not comply with conditions under income tax law. This paper describes how to determine someone, corporation, or non-profit organization should commence or end in performing tax obligations.